2018
DOI: 10.1126/sciadv.aao3225
|View full text |Cite
|
Sign up to set email alerts
|

Systematic deficiency of aftershocks in areas of high coseismic slip for large subduction zone earthquakes

Abstract: Aftershock deficiency in large-slip zones of major subduction zone earthquake ruptures indicates below-critical shear stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 37 publications
18
65
1
Order By: Relevance
“…Besides the 2016 sequence, Trugman and Shearer () observed that the stress drops of these mainshocks are quite large, which is consistent with the generally large mainshock‐aftershock distances of all examined aftershock sequences (Figure ). Similar observations for global megathrust earthquakes were analyzed by Wetzler et al ().…”
Section: Resultssupporting
confidence: 83%
“…Besides the 2016 sequence, Trugman and Shearer () observed that the stress drops of these mainshocks are quite large, which is consistent with the generally large mainshock‐aftershock distances of all examined aftershock sequences (Figure ). Similar observations for global megathrust earthquakes were analyzed by Wetzler et al ().…”
Section: Resultssupporting
confidence: 83%
“…Almost all the early aftershocks (within 3 days) of the Guthrie event are located at the periphery of the inferred rupture model (Figure ), indicating a possible causal dynamic and/or static triggering effects. The absence of early aftershocks in our modeled rupture area suggests an anticorrelation of aftershock productivity with the slip distribution, which was also observed for earthquakes in various tectonic settings (e.g., Mendoza & Hartzell, ; Ross et al, ; Wetzler et al, ; Wu et al, ). The framework that combines stress transfer and source directivity (e.g., Convertito et al, ) may be further improved by incorporating pore pressure increase and poroelastic stress changes due to injection to better explain triggering mechanisms of induced earthquakes.…”
Section: Discussionsupporting
confidence: 78%
“…Few aftershocks occurred below 8 km depth, and no aftershocks surround the areas of higher slip on the deeper parts of the fault. Aftershock distribution from the Pawnee earthquake differs from observations from other earthquakes, for which most aftershocks occur outside of the regions of high slip (e.g., Mendoza & Hartzell, 1988;Wetzler et al, 2018).…”
Section: Finite-fault Rupture Modelmentioning
confidence: 67%